2011
DOI: 10.1016/j.micres.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of methanogenic archaea in a biogas reactor fed with swine feces as the mono-substrate by mcrA analysis

Abstract: Methanogenesis from the biomass in the anoxic biogas reactors is catalyzed by syntrophic cooperation between anaerobic bacteria, syntrophic acetogenic bacteria and methanogenic archaea. Understanding of microbial community composition within the biogas reactors may improve the methane production from biomass fermentation. In this study, methanogenic archaea diverity of a biogas reactor supplied with swine feces as mono-substrate under mesophilic conditions was investigated. Community composition was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 40 publications
2
26
0
1
Order By: Relevance
“…Stoichiometric modeling (56,57) and measurements of natural methanogenic systems (58) have been used to predict acetate accounts for ϳ70% of methane production, and a meta-analysis of anaerobic digester studies found that the acetoclastic genus Methanosaeta accounted for 55% of archaea (although a large proportion of sequences were unclassifiable to genus) (5). However, several studies of biogas reactors have identified a dominance of hydrogenotrophic methanogens, though the relative proportions of Methanobacteriales and Methanomicrobiales vary (41,42,46). In the present study, mcrA-based taxonomic classification suggested the SWH and YL digesters had large or dominant populations of acetoclastic Methanosarcinales, while GZ and ST were dominated by hydrogenotrophic Methanomicrobiales.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…Stoichiometric modeling (56,57) and measurements of natural methanogenic systems (58) have been used to predict acetate accounts for ϳ70% of methane production, and a meta-analysis of anaerobic digester studies found that the acetoclastic genus Methanosaeta accounted for 55% of archaea (although a large proportion of sequences were unclassifiable to genus) (5). However, several studies of biogas reactors have identified a dominance of hydrogenotrophic methanogens, though the relative proportions of Methanobacteriales and Methanomicrobiales vary (41,42,46). In the present study, mcrA-based taxonomic classification suggested the SWH and YL digesters had large or dominant populations of acetoclastic Methanosarcinales, while GZ and ST were dominated by hydrogenotrophic Methanomicrobiales.…”
Section: Discussionmentioning
confidence: 42%
“…However, OTU mcrA richness was also high relative to comparable studies using the 97% sequence similarity threshold. For example, a study of 118 mcrA sequences from an anaerobic batch reactor identified 21 OTU mcrA at an estimated 90% coverage of total richness (20), whereas a study of 123 mcrA clones from an anaerobic biogas reactor identified 28 OTU mcrA at 89% estimated coverage (42). It is therefore possible that the digesters selected for the present study are more diverse than others previously reported on.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Several recent studies have found that the hydrogenotrophic pathway and the Methanoculleus genus were predominant in reactors fed with liquid swine manure (46,47) or with manures mixed with other agricultural wastes (48,49). Not only are Methanoculleus spp.…”
Section: Discussionmentioning
confidence: 99%